Magnetic Resonance Imaging of Clubfoot Treated With the Ponseti Method: A Short-Term Outcome Study - Zhang, Jiangchao; Wang, Ningqing; Lv, Haixiang; Liu, Zhenjiang (Frontiers in Pediatrics, 2022)
Objective To quantitatively evaluate the effectiveness of the Ponseti method for the correction of clubfoot, we decided to use magnetic resonance imaging (MRI) to evaluate changes in the tarsal bone relationship. Methods This is a retrospective study of fifteen children with clubfeet who were treated with the Ponseti method. MRI studies were obtained using a 3.0T Machine (GE Healthcare, United States). T1-weighted and T2-weighted images were acquired in the standard anatomic sagittal, transverse, and coronal planes. For the measurement, the best slice that clearly demonstrated the anatomy was chosen. Sagittal talocalcaneal angle, sagittal tibiocalcaneal angle, coronal tibiocalcaneal angle, transverse talar neck angle, transverse talonavicular angle, and transverse talocalcaneal angle were measured. The eighteen corrected clubfeet were compared with the twelve unilateral normal feet at clinical and radiological levels using a Pirani scoring system and MRI, respectively. Results In total, 15 cases (twelve boys and three girls) with clubfeet were examined by using MRI. Twelve cases had unilateral and three had bilateral involvement (eleven left clubfeet and seven right clubfeet), giving a total of eighteen clubfeet when compared with twelve normal feet. The mean age of patients at examination was 47.7 months (8–96 months). The recovery of the corrected clubfoot in these patients met the goals of Ponseti treatment (functional, normal looking, pain-free, and plantigrade foot). Before Ponseti treatment, the mean Pirani score of clubfoot was 5.5 (5–6). During this follow-up, the Pirani score was 0.07 (0–0.05). The results of the MRI indicated that only the transverse talonavicular angle showed a significant difference between the treated clubfeet and the normal feet (p < 0.001). One case had dorsal talonavicular subluxation in the sagittal plane and had the lateral subluxation of the navicular in the transverse plane, which has never been reported in previous studies. Conclusion Although the appearance and function of clubfoot were recovered well after the Ponseti method, the results of MRI indicated that the Ponseti method successfully corrected the varus, cavus, and equinus deformities and incompletely corrected the adduction deformity regarding transverse talonavicular angle. At the same time, the Ponseti method may cause dorsal talonavicular subluxation in the sagittal plane and lateral subluxation of the navicular in the transverse plane on MRI.